Quotas and Voice : A Possible Package of Reforms. (Policy Papers; Policy Paper ;, 2006)
On July 5, the Executive Board had an informal discussion of reforms of quotas and voice as part of the process of formulating reform proposals for the Annual Meetings in Singapore. That discussion confirmed the importance attached by the membership to reaching agreement on a package of quota and voice reforms in Singapore for the Fund's continued credibility and effectiveness. The discussion also revealed broad support for a reform package along the lines suggested in the staff paper. The support for quota and voice reform across a broad spectrum of the membership indicates that these reforms are not seen as a zero sum game, but rather as change that will strengthen the Fund and from which all members will benefit.